Comparison of Regularly Scheduled Ibuprofen Versus "Pro Re Nata" for Ankle Sprains in Children Treated in the Emergency Department: A Randomized Controlled Trial. Issue 12 (December 2020) - Lim, Rodrick; Sangha, Gurinder; Lepore, Natasha; Bartlett, Katelyn M.; Seabrook, Jamie A.; Rieder, Michael
Abstract : Objective: We compared pain and degree of disability in patients with acute ankle sprains receiving regular scheduled ibuprofen versus pro re nata (PRN). Methods: This study is a randomized single-blinded controlled trial of children aged 7 to 17 years presenting with acute ankle sprain to an emergency department. Patients were randomized to receive 10 mg/kg of ibuprofen per dose (maximum 600 mg) every 6 hours regular scheduled versus PRN. Outcome measures included a 100-mm visual analog scale pain and degree of disability at day 4. A sample size of 72 children had a power of 80% to detect a clinically meaningful difference of 20 mm between the regular and PRN group. Results: We randomly assigned 99 patients to receive regular scheduled (n = 50) or PRN (n = 49) ibuprofen. Pain scores and degree of disability at day 4 showed no significant differences between groups. The rate of reported adverse effects was higher in the regular scheduled group (11.4% vs 9.5%) versus the PRN group. Conclusions: Our study suggests that there is little benefit from routinely using a regular scheduled ibuprofen regimen for acute pediatric ankle sprains.